Modeling and kinetics study of Avocado oil extraction from Madagascar using different mathematical models. - Andrianony Fara Arimalala; Ravelonandro Pierre Hervé; Rajaona Rafihavanana (South African Journal of Chemical Engineering, 2022)
Avocado pulp contains variable oil contents, and is widely used in human nutrition, pharmaceutical and cosmetic industries. This study aims to determine and verify the effects of temperatures (60 °C, 65 °C, 70 °C) and reaction times (6 h, 9 h and 12 h) on the solid liquid extraction of three varieties of oil (Fuerte, Fucca, Bacon) of avocado (Persea americana) from Madagascar. Then, kinetic of oil extraction of one the three varieties, notably the Bacon as most content oil between the three varieties has been investigated using Soxhlet and hexane as solvents to extract oil. Different mathematical models based on second order, Peleg's and logarithmic models could describe the extraction process of avocado. The kinetic of oil extraction from avocado oil by solvent extraction proved that the second order model with high R2 value of 0,9979 is better than Peleg's with R2 value 0,861 and logarithmic model with R2 value 0,893. Therefore, it can be assumed that, comparing the results of both kinetic models (Peleg's and logarithmique models), the second order kinetic model represents well the experimental results of the avocado oil extraction. The optimum condition on yield oil for all varieties (Fuerte, Fucca and Bacon) was found at 70 °C and 12 h (58,14%, 33%, 61,51%).